John Campbell Brown OBE (1947–2019). Issue 2 (1st April 2020) - Fletcher, Lyndsay; Labrosse, Nicolas; Mackinnon, Alexander
Abstract : John Campbell Brown, Alan S Rodger, Thomas Richard (Dick) Carson, Johannes Geiss Abstract: Astronomer Royal for Scotland and inspirational solar physicist, by Lyndsay Fletcher, Nicolas Labrosse and Alec MacKinnon.